Evaluation of Carbon Nanoparticle Suspension and Methylene Blue Localization for Preoperative Localization of Nonpalpable Breast Lesions: A Comparative Study - Yeqing Zhou (Frontiers Media S.A., 2021)
Background: The resection of nonpalpable breast lesions (NPBLs) largely depends on the preoperative localization technology. Although several techniques have been used for the guidance of NPBL resection, more comfortable and effective methods are needed. This aim of this study was to evaluate the use and feasibility of carbon nanoparticle suspension (CNS) and methylene blue (MB)-guided resection of NPBL, to introduce alternative techniques.Methods: A total of 105 patients with 172 NPBLs detected by breast ultrasound were randomized to CNS localization (CNSL) group and MB localization (MBL) group. The injection times of the two groups were divided into 2, 4, 6, 12, 16, and 20 h before surgery. In this study, localization time, stained area, operation time, total resection volume (TRV), calculated resection ratio (CRR), and pathological diagnosis were assessed.Results: All of the 172 lesions were finally confirmed benign. Dye persisted in all cases in the CNSL group (109/109, 100%), while that persisted in only 53 cases in the MBL group (53/63, 84.1%) (P < 0.001). There was a significant correlation between dyeing time and dyeing area in the MBL group (r = −0.767, P < 0.001); however, there was no significant correlation in the CNSL group (r = −0.154, P = 0.110). The operation time was 11.05 ± 3.40 min in the CNSL group and 13.48 ± 6.22 min in the MBL group (P < 0.001). The TRV was 2.51 ± 2.42 cm3 in the CNSL group and 3.69 ± 3.24 cm3 in the MBL group (P = 0.016). For CRR, the CNSL group was lower than the MBL group (7.62 ± 0.49 vs. 21.93 ± 78.00, P = 0.018). There is no dye remained on the skin in the MBL group; however, dye persisted in 12 patients (19.4%) in the CNSL group (P = 0.001).Conclusion: Carbon nanoparticle suspension localization and MBL are technically applicable and clinically acceptable procedures for intraoperatively localizing NPBL. Moreover, given the advantages of CNSL compared to MBL, including the ability to perform this technique 5 days before operation and smaller resection volume, it seems to be a more attractive alternative to be used in intraoperative localization of NPBL.